2022
DOI: 10.48550/arxiv.2208.05700
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On interactions of massless spin 3 and scalar fields

Abstract: Using new approach for the deformation procedure in the case of reducible gauge theories (Lavrov in Eur. Phys. J. C 82:429, 2022), it is shown that in the model of massless spin 3 fields and a real scalar field local cubic vertices invariant under initial gauge transformations do not exist while local quartic gauge-invariant vertices can be constructed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…It was shown that cubic vertices invariant under original gauge transformations are forbidden while local gauge-invariant quartic vertices are explicitly found. In the present paper, we extend the results [35,36] up to quintic vertices.…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…It was shown that cubic vertices invariant under original gauge transformations are forbidden while local gauge-invariant quartic vertices are explicitly found. In the present paper, we extend the results [35,36] up to quintic vertices.…”
Section: Introductionsupporting
confidence: 76%
“…describing interactions among the massless spin 3 and real scalar fields in the fifth order. By the same reasons explained in [35,36], the gauge algebra does not deform under special anticanonical transformations (3) so that the deformed action is invariant under gauge transformations (2), δ S[ϕ, φ] = 0. Due to the locality of original gauge transformations, the action S 3 loc [ϕ, φ] should be also gauge-invariant, δS 3 loc [ϕ, φ] = 0.…”
Section: Vertices ∼ ϕφφφφmentioning
confidence: 99%
See 2 more Smart Citations
“…In the framework of the BRST approach, the higher spin fields appear as the coefficients in the vectors of the Fock Footnote 1 continued to construct the higher spin field vertices [37,38]. We also point out a new approach to problem of locality in the higher spin field theory that can be related with a structure of the interaction vertices [39].…”
Section: Brst Charge and Free Lagrangianmentioning
confidence: 99%